Analysis of Training Participants' Responses to Training Activities with the Theme "ICT-Based Innovative Learning" - Kusumah, Raden Gamal Tamrin; Risdianto, Eko (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2022)
This study aims to determine the response of training participants to training activities with the theme "ICT-based innovative learning" at Fatmawati Sukarno State Islamic University. This type of research is survey research. The research sample was 10 people who were trainees with the theme "ICT-based innovative learning" at Fatmawati Sukarno State Islamic University. The study was conducted in October 2022. The data collection technique used a questionnaire made with a modified Likert scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. The results showed thatthe training participants gave a very positive response to the training activities with the theme "Innovative ICT-based learning" which had been carried out at Fatmawati Sukarno State Islamic University.